Parameter optimisation for mitigating somatosensory confounds during transcranial ultrasonic stimulation - Benjamin R. Kop; Linda de Jong; Butts Pauly Kim; Hanneke E.M. den Ouden; Lennart Verhagen (Brain Stimulation, 2025)
Background: Transcranial ultrasonic stimulation (TUS) redefines what is possible with non-invasive neuromodulation by offering unparalleled spatial precision and flexible targeting capabilities. However, peripheral confounds pose a significant challenge to reliably implementing this technology. While auditory confounds during TUS have been studied extensively, the somatosensory confound has been overlooked thus far. It will become increasingly vital to quantify and manage this confound as the field shifts towards higher doses, more compact stimulation devices, and more frequent stimulation through the temples where co-stimulation is more pronounced. Methods: Here, we provide a systematic characterisation of somatosensory co-stimulation during TUS. We also identify the conditions under which this confound can be mitigated most effectively by mapping the confound-parameter space. Specifically, we investigate dose-response effects, pulse shaping characteristics, and transducer-specific parameters. Results: We demonstrate that somatosensory confounds can be mitigated by avoiding near-field intensity peaks in the scalp, spreading energy across a greater area of the scalp, ramping the pulse envelope, and delivering equivalent doses via longer, lower-intensity pulses rather than shorter, higher-intensity pulses. Additionally, higher pulse repetition frequencies and fundamental frequencies reduce somatosensory effects. Through our systematic mapping of the parameter space, we also find preliminary evidence that particle displacement (strain) may be a primary biophysical driving force behind peripheral somatosensory co-stimulation. Conclusion: This study provides actionable strategies to minimise somatosensory confounds, which will support the thorough experimental control required to unlock the full potential of TUS for scientific research and clinical interventions.